A 5‐year retrospective review of skin adnexal tumours received at a tertiary dermatopathology service: implications for linked genetic diagnoses. (21st October 2021) - Cook, S.; Bajwa, D.; Hollestein, L.; Husain, A.; Rajan, N.
Summary: Background: Skin adnexal tumours (SATs) comprise a diverse range of neoplasms, which are difficult to diagnose clinically. They present in paediatric and adult populations, and may be indicative of an underlying genetic syndrome. There is a lack of recent data on the presentation of these tumours in clinical practice in European populations. Objectives: To characterize the clinical and pathological features of SATs received at a single tertiary centre over a 5‐year period. Methods: A retrospective health record audit of SATs received at the Department of Cellular Pathology, Royal Victoria Infirmary, Newcastle upon Tyne Hospitals NHS Foundation Trust, during the period November 2012 to October 2017 was performed. Results: In total, 107 144 skin cases were received during the audit period. A total of 1615 cases of SATs from 1359 patients were included; 1570 (97·2%) were benign and 45 (2·8%) were malignant. Overall, the average age at presentation was 55 years (range 11 months to 97 years) and the male to female ratio was 0·77 : 1. Sweat gland and hair follicle SATs were most frequently excised; in adults, the most frequent tumour was hidrocystoma, and in children, pilomatrixoma occurred most often. Prebiopsy diagnosis was correct in 28% of cases. Benign SATs are often markers of an associated genetic condition, which warrants improved discrimination of sporadic from genetically related SATs. Conclusions: SATs are difficult to diagnose clinically, and clinicopathological correlation may help enhance discrimination of genetically related SATs from sporadic cases. These data have implications for clinical and dermatopathological training provision, the development of reporting standards, and genetic assessment of selected patients. Abstract : What is already known about this topic? Skin adnexal tumours (SATs) comprise a diverse range of neoplasms, which arise from the hair follicle, sebaceous and eccrine glands. Clinical diagnosis is difficult owing to the lack of discriminatory features. Selected SATs are recognized markers of underlying genetic conditions, but the proportion of these tumours occurring in unselected European populations is not known. What does this study add? Prebiopsy diagnosis of SATs was correct in only 28% of cases. Clinicopathological correlation may aid discrimination of sporadic from genetically related SATs, with implications for genetic testing and cancer screening. Pathology reports of SATs that flag known linked genetic diagnoses to the referring surgeon should be part of the standard of care for patients from whom SATs are excised. Linked Comment: Z. Marušić and E. Calonje. Br J Dermatol 2022; 186:16–17 . Plain language summary available online